Sustainable control of malaria employing Gambusia fishes as biological control in Jalore and Barmer districts of Western Rajasthan - Himmat Singh; Sanjeev Kumar Gupta; Kumar Vikram; Rekha Saxena; Aruna Srivastava; B N Nagpal (Journal of Vector Borne Diseases, 2022)
Sardar Sarovar Irrigation Canal system was constructed by Narmada Valley Development Authority (NVDA) to cater to drinking water as well as for irrigation purposes in Jalore and Barmer districts of Western Rajasthan. To cater to the needs of water for the villagers in the command areas, ‘Diggies’ (surface water tanks) with ‘Sumpwells’ (water supply surface tanks) were installed. In a health impact assessment study of the irrigation canals from December 2010 to February 2016, the breeding of two major malaria vectors. An. culicifacies and An. stephensi were observed in diggies and sumpwells. As a biological control, Gambusia affanis fishes were employed for larval control in such stagnated water sites during the intervention phase viz. February 2012 in 251 diggies and 251 sumpwells. A significant reduction of breeding in diggies (99.54%) and sumpwells (97.81%) was observed. The positivity and larval density (dip index) were monitored in the control from up to February 2016 for their sustainability.